The effects of methylprednisolone and halofuginone on preventing esophageal and hypopharyngeal fibrosis in delivered radiotherapy - Dabak, Hakan; Karlidag, Turgut; Akpolat, Nusret; Keles, Erol; Alpay, Hayrettin Cengiz; Serin, Meltem; Isik, Ozgur (Springer, 2010)
In this study, we assessed the effects of halofuginone and methylprednisolone on hypopharyngeal and esophageal stricture that can develop following radiation to the head and neck of rats. Rats were divided into four groups randomly and 18 Gy radiation was given to the head and neck regions of all rats except the control group. Group 1 (Control Group): No radiation or drugs were administered. Group 2 (Radiation Group): only radiation was applied without any drugs. Group 3 (Halofuginone Group): halofuginone 100 mu g/kg per day was given intraperitoneally. Group 4 (Methylprednisolone Group): methylprednisolone 1 mg/kg per day was administered intramuscularly. In all groups, 90 days after application of radiation, sections of the proximal esophagus and hypopharynx were examined for fibrosis, fibroblast proliferation, vascularization, epithelial atypia, necrosis, polymorphonuclear leukocytes, mononuclear cells, and stenosis index by light microscope and the hydroxyproline levels were assessed biochemically. Fibrosis, epithelial atypia and hydroxyproline levels were found to be significantly higher in the radiation group compared to the control group (P < 0.05). We did not observe fibrosis in either the halofuginone or the control groups. Fibrosis was also significantly lower in the methylprednisolone group than the radiation group (P < 0.05). The differences of the stenosis index scores between the groups were not statistically significant (P < 0.05). Vascularization was similar in all groups. We think that especially halofuginone is a drug that can be used safely to prevent fibrosis due to radiotherapy, but further studies are needed.
Keywords: Radiation; Esophagus; Halofuginone; Fibrosis; Hydroxyproline